2009
DOI: 10.1007/s10048-009-0223-z
|View full text |Cite
|
Sign up to set email alerts
|

Progressive retinal atrophy in Schapendoes dogs: mutation of the newly identified CCDC66 gene

Abstract: Canine generalized progressive retinal atrophy (gPRA) is characterized by continuous degeneration of photoreceptor cells leading to night blindness and progressive vision loss. Until now, mutations in 11 genes have been described that account for gPRA in dogs, mostly following an autosomal recessive inheritance mode. Here, we describe a gPRA locus comprising the newly identified gene coiled-coil domain containing 66 (CCDC66) on canine chromosome 20, as identified via linkage analysis in the Schapendoes breed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
50
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(54 citation statements)
references
References 28 publications
3
50
0
1
Order By: Relevance
“…The CEP72 BioID hits also include proteins that were not previously implicated in ciliogenesis. Among these hits is the retinal degeneration gene CCDC66 (Dekomien et al, 2010;Gerding et al, 2011). CCDC66 has been reported to localize to centriolar satellites (Gupta et al, 2015) and its mRNA has been found to interact with microtubules in a screen for microtubule-binding transcripts in Xenopus laevis egg extracts (Sharp et al, 2011).…”
Section: Proximity Mapping Identifies New Centriolar Satellite Proteinsmentioning
confidence: 99%
See 3 more Smart Citations
“…The CEP72 BioID hits also include proteins that were not previously implicated in ciliogenesis. Among these hits is the retinal degeneration gene CCDC66 (Dekomien et al, 2010;Gerding et al, 2011). CCDC66 has been reported to localize to centriolar satellites (Gupta et al, 2015) and its mRNA has been found to interact with microtubules in a screen for microtubule-binding transcripts in Xenopus laevis egg extracts (Sharp et al, 2011).…”
Section: Proximity Mapping Identifies New Centriolar Satellite Proteinsmentioning
confidence: 99%
“…Expression studies in dog and mouse tissues via quantitative realtime RT-PCR (qRT-PCR) (Dekomien et al, 2010) and a genomewide analysis of transcription profiles (Krupp et al, 2012) showed that CCDC66 is not only expressed in retina but most tissues including heart, brain, liver and blood. Immunoblotting with an antibody against CCDC66 in RPE1, HeLa and HEK293T cell extracts validated the wide expression profile of CCDC66 ( Fig.…”
Section: Proximity Mapping Identifies New Centriolar Satellite Proteinsmentioning
confidence: 99%
See 2 more Smart Citations
“…Os testes genéticos são exames laboratoriais que possibilitam a análise de DNA, RNA, cromossomos, proteínas e certos metabólitos do paciente, com o objetivo de detectar a presença de material genético, que pode estar (ou não) relacionado às doenças genéticas e hereditárias em geral (DEKOMIEN et al, 2010;MELLERSH, 2012). Diversas formas de degeneração retiniana são causadas por alterações genéticas.…”
Section: Testes Genéticosunclassified